2014
DOI: 10.1007/8904_2014_315
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Antipsychotic Medication Use in Monoallelic GBA-Related Parkinson Disease

Abstract: Mutations in glucosidase, beta, acid (GBA) are associated with cognitive impairment in Parkinson disease (PD) as well as dementia with Lewy bodies. For both of these diseases, dementia and hallucinations are typically treated with cholinesterase inhibitors and antipsychotics. However, in some lysosomal storage disorders certain antipsychotic medications are poorly tolerated. This study examined cholinesterase inhibitor and antipsychotic use in monoallelic GBA-related PD to explore potential pharmacogenetic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Patients who carry GBA1 mutations present a higher prevalence and severity of bradykinesia, motor complications, hyposmia, autonomic impairment, sexual dysfunction, hallucinations, cognitive decline, depression and anxiety (Alcalay et al, 2012;Beavan and Schapira, 2013;Brockmann et al, 2011;Lesage et al, 2010;Li et al, 2014;McNeill et al, 2012;Wang et al, 2014;Winder-Rhodes et al, 2013;Zokaei et al, 2014). Because of the increased rate of clinical decline, patients with GBA1 mutations often initiate therapies earlier compared with non-mutation carriers (Angeli et al, 2013;Barrett et al, 2014).…”
Section: Clinical Features Of Gaucher-related Pdmentioning
confidence: 97%
“…Patients who carry GBA1 mutations present a higher prevalence and severity of bradykinesia, motor complications, hyposmia, autonomic impairment, sexual dysfunction, hallucinations, cognitive decline, depression and anxiety (Alcalay et al, 2012;Beavan and Schapira, 2013;Brockmann et al, 2011;Lesage et al, 2010;Li et al, 2014;McNeill et al, 2012;Wang et al, 2014;Winder-Rhodes et al, 2013;Zokaei et al, 2014). Because of the increased rate of clinical decline, patients with GBA1 mutations often initiate therapies earlier compared with non-mutation carriers (Angeli et al, 2013;Barrett et al, 2014).…”
Section: Clinical Features Of Gaucher-related Pdmentioning
confidence: 97%
“…This includes worse performance on broad screening measures of cognitive functioning (e.g., the Montreal Cognitive Assessment; Brockmann et al, 2011), and more specifically, deficits in visual short-term memory (Zokaei et al, 2014), memory and visuospatial functioning (Alcalay et al, 2012; Mata et al, 2016), and executive functioning and working memory (Mata et al, 2016). In addition, GBA -PD is related to neuropsychiatric symptoms such as depression and anxiety (Brockmann et al, 2011; Swan et al, 2016), and those with GBA -PD are more likely to have hallucinations and sustained cholinesterase inhibitor use (Barrett et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…GBA-mutation PD patients appeared to have a higher risk of reporting hallucinations when compared to idiopathic PD patients, but no differences between mild and severe mutations were found [73]. A statistically significant higher frequency of hallucinations in PD patients with GBA mutation was not confirmed in all studies [62,72].…”
Section: Non Motor Featuresmentioning
confidence: 93%
“…However, significant differences in cognitive function between PD patients with and without GBA mutations were not confirmed in some studies [13,62,71,72]. It has been reported that there is significantly higher frequency of usage of acetylcholine esterase inhibitors for dementia in GBA PD compared with idiopathic PD [73], and one study found significant differences in selfreported cognitive impairment [74]. PD patients with GBA mutation also showed a more rapid cognitive decline [51,52,54], although this evidence was not supported by all studies [69].…”
Section: Non Motor Featuresmentioning
confidence: 96%